1979
DOI: 10.1093/infdis/140.4.500
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cellular Immunity to Cytomegalovirus in Congenitally Infected Children and Their Mothers

Abstract: Cell-mediated immunity to cytomegalovirus (CMV) was determined in congenitally infected children and their mothers by use of assays for CMV-specific lymphocyte blastogenesis and interferon production. Six viruric children responded poorly in both assays. Two older nonviruric children responded in the blastogenesis assay, and lymphocytes from one of them produced interferon. Mothers of older children usually responded in the blastogenesis assay, but only one of them produced interferon. Mothers whose infected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

1980
1980
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 13 publications
3
34
0
2
Order By: Relevance
“…This latter observation confirms previous studies' findings of long-lasting suppression of lymphocyte blastogenic responses to HCMV in adults after mononucleosis [25] and in adolescents after asymptomatic primary HCMV infection [4]. Similar findings were observed in babies with perinatal or postnatal HCMV infection [26,27], in congenitally infected children, and in their mothers [28][29][30][31].…”
Section: Discussionsupporting
confidence: 91%
“…This latter observation confirms previous studies' findings of long-lasting suppression of lymphocyte blastogenic responses to HCMV in adults after mononucleosis [25] and in adolescents after asymptomatic primary HCMV infection [4]. Similar findings were observed in babies with perinatal or postnatal HCMV infection [26,27], in congenitally infected children, and in their mothers [28][29][30][31].…”
Section: Discussionsupporting
confidence: 91%
“…In cell culture, CMV is less destructive than other viruses known to infect man and this is probably related to its capacity to energize the host cell (Isom, 1979). The long term nature of CMV infections in young children, often amounting to the first years of life (Stagno et al, 1975), may be related to the longevity of infected cells in rico with possible protection from the host's immune response (Gehrz et al, 1977;Starr et al, 1979). Assuming cell viability, it is conceivable that infected cells could be rescued from virus control as a consequence of the action of selective antiviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated previously that lymphocytes from patients with congenital CMV infection generally lack proliferative responses to CMV in vitro [Gehrz et al, 1977[Gehrz et al, , 1982Reynolds et al, 1979;Starr et al, 1979] and production of interferon (IFN) in response to CMV antigens [Gehrz and Leonard, 1985]. Impairment in antigen recognition appears to be CMV-specific because a proliferative response is exhibited to mitogens [Gehrz et al, 1977].…”
Section: Introductionmentioning
confidence: 99%